Advanced Structural and Functional Materials. - Chun, Sangeun; Salem, Abdel-Badeeh Mohamed; Gorlatch, Sergei (Zurich : Trans Tech Publications, Limited, 2021)
Special topic volume with invited peer-reviewed papers only.
Effect of Detergent on Concrete prepared with Periwinkle shell as Coarse Aggregate -- The Effectiveness of Basalt Fiber in Lightweight Expanded Clay to Improve the Strength of Concrete Helicoidal Staircase -- Effects of Shear Deformation of Struts in Hexagonal Lattices on their Effective In-Plane Material Properties -- Chemical Kinetics Modeling on Bio-Oil Production from Pyrolysis of Sugarcane Bagasse -- Optimization of Normal and Submerged FSP Parameters for Dissimilar Aluminium Joints Using Taguchi Technique -- Keyword Index -- Author Index
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Materials -- Congresses; Building materials -- Congresses; Composite materials; Matériaux -- Congrès.; Construction -- Matériaux -- Congrès.; Composites; composite material; Building materials; Materials; Conference papers and proceedings